Process documentation of selecting the ultra poor for CFPR/TUP Programme - Noor, Marufia; Mamun-ur-Rashid; Shihab, Abu Muhammad; Parveen, Rezvina; Rahman, Hasanur; Ali, Tariq (BRAC Research and Evaluation Division (RED), 2020)
ll1e targeting process for the CFPR/TUP programme aims to bring together diverse strands of knowledge on poverty (indigenous, local, programmatic and academic) in identifying and selecting CFPR/TUP beneficiaries (tvfatin and Halder 2002). The targeting process is, therefore, multi-staged and involves a variety of actors and processes. The targeting process has four stages. Through each stage of the targeting process, diverse streams of knowledge arc combined to identify a smaller and more defined sample from which ultra poor beneficiaries may be selected. The following are the targeting stages: Rapport Building PRA Meeting Survey and Preliminary Selection Final Selection Four researchers were trained in Dhaka in Process Documentation Research (PDR) specifically and Qualitative Research, generally. They were then sent to PDR sites around the country to document the various stages of the targeting process. In between March 19, 2003 and April 30, 2003, the researchers sent back 28 reports covering 108 events/activities/stages to the Head Office. These process documentation reports have been consolidated into this final report. The process documentation revealed the wealth and diversity of activities and interactions that constitute the various stages of the targeting process. We shall look at the trends and patterns in each of these stages separately, before commenting on the broader themes and issues that ha,·e emerged from the process documentation.